2021
DOI: 10.1080/09537104.2021.1945571
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation by charged ligands and nanoparticles: platelet glycoprotein receptors as pattern recognition receptors

Abstract: Charge interactions play a critical role in the activation of the innate immune system by damage-and pathogen-associated molecular pattern receptors. The ability of these receptors to recognize a wide spectrum of ligands through a common mechanism is critical in host defense. In this article, we argue that platelet glycoprotein receptors that signal through conserved tyrosine-based motifs function as pattern recognition receptors (PRRs) for charged endogenous and exogenous ligands, including sulfated polysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 117 publications
(140 reference statements)
0
12
0
Order By: Relevance
“…Glycoprotein VI (GPVI) is a platelet immunoglobulin receptor which is known as a receptor for collagen [ 5 ], but in recent years has also been shown to be a receptor for fibrin and fibrinogen, among other predominantly charged ligands [ 6 ]. In vitro flow studies have shown that GPVI contributes to the stability of newly formed platelet aggregates on collagen at high shear through use of the blocking anti-GPVI Fab ACT017, which has more recently been named glenzocimab [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glycoprotein VI (GPVI) is a platelet immunoglobulin receptor which is known as a receptor for collagen [ 5 ], but in recent years has also been shown to be a receptor for fibrin and fibrinogen, among other predominantly charged ligands [ 6 ]. In vitro flow studies have shown that GPVI contributes to the stability of newly formed platelet aggregates on collagen at high shear through use of the blocking anti-GPVI Fab ACT017, which has more recently been named glenzocimab [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Montague et al (2021) have proposed the three platelet ITAM receptors as PRRs as they are activated by a miscellaneous group of polyvalent charged ligands. 14 The charged nature of katacine is consistent with this mechanism. However, we did not observe clear phosphorylation on the FcR gamma chain (∼15 kDa) on whole lysates when treated with katacine, while a marked increase on the phosphorylation was observed when platelets were treated with the GPVI ligand, CRP.…”
Section: Discussionmentioning
confidence: 59%
“…12,13 The dependency on the four charged residues has led to the hypothesis that CLEC-2 may be a pattern recognition receptor (PRR) on platelets. 14 The identification of small-molecule ligands for CLEC-2 is essential for the development of orally available inhibitors as this is the preferred route of delivery for long-term antithrombotics. To address this objective, we set up a highthroughput screening (HTS) assay using a small-molecule library based on the podoplanin-CLEC-2 interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems counterintuitive but could be explained by previous animal studies showing that UFP exposure caused thrombotic and inflammatory effects at different lags [ 18 , 51 , 52 ]. However, there is also some evidence that exposure to UFP can increase thrombus formation independent of inflammation [ 53 ], as nanoparticles may penetrate into the blood circulation with the potential for direct effects on platelet activation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%